2020
DOI: 10.35627/2219-5238/2020-324-3-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Features of Physical Development of Schoolchildren and Students Engaged in Physical Education and Sports

Abstract: Introduction. A distinctive feature of the modern lifestyle of children and adolescents is insufficient physical activity having a negative effect on their health. We conducted a physical activity survey for 997 schoolchildren and 597 students of the city of Ufa. Results. The results showed that 688 respondents (43.16%) did not do sport outside school or university. 272 people (17.06%) reported jogging and playing sports games on their own. 634 respondents (39.78%) attended sports clubs and sections on a regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In this regard, previous studies have reported that leisure time is the most common time to exercise (Agafonov et al, 2020). Sport is one type of activity that is carried out in organized leisure time and is usually played in a team or individually (Agafonov et al, 2020;Południak et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, previous studies have reported that leisure time is the most common time to exercise (Agafonov et al, 2020). Sport is one type of activity that is carried out in organized leisure time and is usually played in a team or individually (Agafonov et al, 2020;Południak et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, previous studies have reported that leisure time is the most common time to exercise (Agafonov et al, 2020). Sport is one type of activity that is carried out in organized leisure time and is usually played in a team or individually (Agafonov et al, 2020;Południak et al, 2021). The current problem is that sports lessons at school are only done once a week, and the density of other subjects causes regular exercise to be neglected.…”
Section: Introductionmentioning
confidence: 99%